Objective versus Subjective Assessment of Laparoscopic Skill. (2nd July 2013) - van Empel, Pieter J.; van Rijssen, Lennart B.; Commandeur, Joris P.; Verdam, Mathilde G. E.; Huirne, Judith A.; Scheele, Fedde; Bonjer, H. Jaap; Meijerink, W. Jeroen
Abstract : Background . The equality of subjective- and objective-assessment methods in laparoscopic surgery are unknown. The aim of this study was to compare a subjective assessment method to an objective assessment method to evaluate laparoscopic skill. Methods . A prospective observational cohort study was conducted. Seventy-two residents completed a basic laparoscopic suturing task on a box trainer at two consecutive assessment points. Laparoscopic skill was rated subjectively using the Objective Structured Assessment of Technical Skills (OSATS) list and objectively using the TrEndo, an augmented-reality simulator. Results . TrEndo scores between the two assessment points correlated. OSATS scores did not correlate between the two assessment points. There was a correlation between TrEndo and OSATS scores at the first assessment point, but not at the second assessment point. Overall, OSATS scores correlated with TrEndo scores. There was a greater spread within OSATS scores compared to TrEndo scores. Conclusion . OSATS scores correlated with TrEndo scores. The TrEndo may be more responsive at rating individual's laparoscopic skill, as demonstrated by a smaller overall spread in TrEndo scores. The additional value of objective assessment methods over conventional assessment methods as provided by laparoscopic simulators should be investigated.